The Effect of Music on Stress Parameters in Acute Stroke - Adamou, Lilia (My University, 2021)
Treatment success and patient recovery are influenced by the physical and psychological stress responses the patient experiences after a sudden stroke event. Research shows that elevated stress levels after stroke are associated with worse recovery and even death. The present block randomized, controlled study (N=16+16) investigates the effect of music intervention on mental, cognitive, and cardiovascular levels of stress in acute stroke patients. Patients of the music group listened to self-selected music intensely during the third post-stroke day. The control group received standard care. Music group showed a significant increase in positive moods, decrease in symptoms of mental distress, and improved cognitive performance compared to controls, as observed immediately after the intervention and even at six-month follow-up. No significant differences were detected in cardiovascular stress between the two groups. These findings are consistent with previous studies confirming beneficial effects of music in neurological patients and are the first to show stress-relieving potency of music in acute stroke. The present study supports the idea of implementing music listening in routine clinical treatment and acute care of stroke.
Keywords: acute stroke, stress, music intervention, mood, cognition, cardiovascular stress.